Effectiveness of the GURAKA Application in Enhancing Maternal Preparedness for Childbirth - Siska Nawang Ayunda Maqfiro Maqfiro; Triany Laila Pelu (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Birth Preparedness and Complication Readiness (BPCCR) is a strategy aimed at promoting planning for childbirth and emergency preparedness among pregnant women, their families, and communities. The study aimed to determine the effectiveness of the GURAKA application on maternal preparedness for childbirth. The study population consisted of third-trimester pregnant women in the service area of Kota Community Health Center. Sixty participants were selected using consecutive sampling and were allocated into two groups: one group used the GURAKA application, while the control group used the MCH Book. Data were analyzed sequentially using test of normality and homogeneity, Wilcoxon Signed Rank Test, and Mann–Whitney U test. The Mann-Whitney analysis showed that, in the pretest, the intervention group demonstrated a higher mean rank (36.32) than the control group (24.68), with the difference being statistically significant (p = 0.009). In the posttest, the intervention group’s mean rank increased to 37.10, while the control group decreased to 23.90, with p = 0.003 (p<0.05). These findings indicate that the GURAKA Application is more effective than the MCH Book in enhancing maternal readiness for childbirth.